ТАРЖИМАДА ХАТО ТУРЛАРИ («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
This article will be devoted to the study of the classification of translation errors, such as linguistic errors made in the target language, depending on the degree of understanding of the original text by the translator. It analyzes the opinions of linguists and translators expressed about the types of errors related to the lexical, grammatical, stylistic level and criteria of translation.
Keywords: linguistic and speech norm, stylistic and syntactic errors, typology of translation errors, hermeneutical approach.